Antroposentrisme dan budaya hukum lingkungan (Studi eksploitasi timah di Belitung Timur) - Haryadi, Dwi; Darwance, Darwance; Saputra, Putra Pratama (PROGRESIF: Jurnal Hukum, 2020)
Mining activities that tend to ignore or even damage the environment indicate an anthropocentrism behavior where human interests take more precedence than the environmental sustainability. Economic interests are often the main reason for mining activity such as cutting down protected forests, damaging and polluting watersheds, and etc. As an area that has been exploited for a long time, East Belitung has experienced the increasing number of its critical land and natural disasters such as floods because of tin mining that ignores the environment. This condition show that the legal culture of the miner's environment has not been developed yet, or it’s already exists but the clash with economic interests and dependence on tin has made anthropocentrism become more dominant. Policies, prevention efforts, socialization and enforcement have been carried out but the fact shows it’s not easy to harmonize between anthropocentrism and awareness of the environmental law of the community..